Yuriy Drozd (dedicated to 75th Birthday) (Algebra and Discrete Mathematics, 2019)
On October 15, 2019 an outstanding Ukrainian mathematician, one of the founders of Kyiv algebraic school Yuriy Drozd celebrated his 75th birthday.